Maragheh City: Geography, History and Culture - Y. P. Ivanova (Научный диалог, 2017)
The review of the book by Azerbaijani researchers Enver Chingisoglu (Ənvər Çingisoğlu) and Mahal Kadzhar (Mahal Qacar) “History of Maragheh,” published in 2016, is presented. The presentation of the content of the publication dedicated to one of the oldest cities in Western Iran and Iranian Azerbaijan is given. The first part of the book based on numerous publications, mostly in Persian language, analyzes the data on the origin of the city, geography of the Maragheh region and the history of Maragheh from antiquity to the 20th century. It is reported that the second part of the book focuses on the historical role of Maragheh in the development of culture of Iran and Azerbaijan.